Abortion Access and Medically Complex Pregnancies Before and After Texas Senate Bill 8. Issue 5 (5th May 2023) - Arey, Whitney; Lerma, Klaira; Carpenter, Emma; Moayedi, Ghazaleh; Harper, Lorie; Beasley, Anitra; Ogburn, Tony; White, Kari
Abstract : Restrictive abortion policies did not align with health care professionals' more nuanced views of options for care and patient autonomy. Abstract : OBJECTIVE: To evaluate how Texas health care professionals who care for patients experiencing medically complex pregnancies navigate abortion restrictions. METHODS: We conducted qualitative in-depth interviews with health care professionals across Texas who cared for patients with life-limiting fetal diagnoses or who had existing or developed health conditions that adversely affected pregnancy. We conducted the first round of interviews March–June 2021 and the second round of interviews January–May 2022 after the implementation of Texas Senate Bill 8 (SB8), which prohibited most abortions after detection of embryonic cardiac activity. We used inductive and deductive qualitative analysis to identify themes and changes in practice after the implementation of SB8. RESULTS: We conducted a total of 50 interviews: 25 before implementation of SB8 and 25 after the law's implementation. We interviewed 21 maternal–fetal medicine specialists, 19 obstetrician–gynecologists, eight physicians whose primary practice is the provision of abortion care, and two genetic counselors. Participants reported presenting their patients with information about health risks and outcomes of continued pregnancy in each policy period; however, counseling on these options was curtailed after implementation of SB8. Even in cases in which a patient's health and, in some cases, life would be compromised, narrow criteria for abortions at hospitals limited care before implementation of SB8, and criteria often became more stringent after implementation of SB8. Administrative approval processes and referrals for abortion delayed care and endangered patients' health, which worsened after in-state options were eliminated after implementation of SB8. Participants noted that patients with more limited resources who were unable to travel out of state often had to continue pregnancies, further increasing their risk of morbidity. CONCLUSION: Texas health care professionals' abilities to provide evidence-based abortion care to patients with medically complex pregnancies were constrained by institutional policies, and care options narrowed further after implementation of SB8. Abortion restrictions limit shared decision making, compromise patient care, and put pregnant people's health at risk.